Career quandaries of activist environmental engineering graduates in Indonesia. Issue 12 (2nd December 2019) - Nilan, Pam; Wibawanto, Gregorius Ragil
Abstract: This article reports on a study that aimed to investigate how young Indonesians might become environmentalists, and what happens when they do. It uses a Bourdieusian framework to analyse interviews with six Indonesian environmental engineering students who took an active role in environmental conservation campaigns while studying at the prestigious University of Technology Bandung (ITB) in Indonesia. In 2014, they were pondering the challenge of negotiating an environmentally defensible career after graduation from their degree. Four years later, in 2018 follow-up contact, it was evident that while they still operated a moral responsibility of conservation and care for the natural world, not all of them had found the dream jobs they imagined as earnest undergraduates keen to protect the natural environment. Yet most had maintained their 'ecological habitus' even as they sought to make good on the institutionalised cultural capital invested in their undergraduate degree in environmental engineering. This article examines that journey.